2013
DOI: 10.1186/1478-811x-11-68
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase activation mediates CCL3-induced cell migration and matrix metalloproteinase-2 expression in human chondrosarcoma

Abstract: Chemokine (C-C motif) ligand 3 (CCL3), also known as macrophage inflammatory protein-1α, is a cytokine involved in inflammation and activation of polymorphonuclear leukocytes. CCL3 has been detected in infiltrating cells and tumor cells. Chondrosarcoma is a highly malignant tumor that causes distant metastasis. However, the effect of CCL3 on human chondrosarcoma metastasis is still unknown. Here, we found that CCL3 increased cellular migration and expression of matrix metalloproteinase (MMP)-2 in human chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…1 The phenotypic features of this tumor, i.e., a dense extracellular matrix, a low percentage of dividing cells, and a poor vascularity, contribute to CHS chemo-and radioresistance. 1,21 The aim of this study was to describe the immune cell infiltrates associated with CHS, and determine their functional role in CHS progression, first in human samples and then a syngeneic rat model. Indeed, CHS is an unfrequent tumor, thus collecting enough non-decalcified FFPE embedded samples to constitute a cohort is quite challenging.…”
Section: Discussionmentioning
confidence: 99%
“…1 The phenotypic features of this tumor, i.e., a dense extracellular matrix, a low percentage of dividing cells, and a poor vascularity, contribute to CHS chemo-and radioresistance. 1,21 The aim of this study was to describe the immune cell infiltrates associated with CHS, and determine their functional role in CHS progression, first in human samples and then a syngeneic rat model. Indeed, CHS is an unfrequent tumor, thus collecting enough non-decalcified FFPE embedded samples to constitute a cohort is quite challenging.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The function of PTEN is displayed through suppressing PI3K, thus the process of PIP2 transform into PIP3 would be blocked, leading the downstream Akt not to be phosphorylated, namely inhibit PI3K/Akt/mTOR (mammalian target of rapamycin, mTOR) 6,7 and other kinds of signal pathways participating in tumor cell proliferation, evasion of apoptosis and resistance to chemotherapy. 8 We learned through literatures that the mRNA expression of chemokines including CCL2, CCL4, CCL3, CXCL, CXCL5, and chemokine receptor CXCR3, was increased in carcinoma tissues of Pten knock out (KO) mice or in cancer cells of siRNA-mediated inhibition of PTEN gene expression, [9][10][11] which have been linked to play precisely domesticated role of the M2 phenotype and thus will likely facilitate development of microenvironment to enhance tumor infiltrating, metastasis and deterioration. 12,13 A considerable amount of information displayed, the decline of PTEN protein in cancer was known to heighten the expression of the angiogenic factor VEGF-A, and there was a negative correlation between PTEN and VEGF-A.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have also shown that AMPK plays an important role in cancer metastasis [ 17 ]. AMPK activation has been reported to mediate chemokine (C-C motif) ligand 3-increased MMP-2 expression and chondrosarcoma metastasis [ 23 ]. However, the effects of AMPK activation on resistin-mediated metastasis and MMP expression in human chondrosarcoma are currently unknown.…”
Section: Introductionmentioning
confidence: 99%